Measuring Ethnopedagogical and Ecological Values of Seven-Flower Rituals in East Javanese Traditional Dance - Afnan, Muhammad Zahrudin; Musthofa, Syafri; Puspitawati, Rinie Pratiwi; Isnawati, Isnawati (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2026)
This study examined the pedagogical and ecological significance of bunga tujuh rupa (seven-flower rituals) in traditional East Javanese dance through an ethnopedagogical approach. Previous studies have primarily documented the cultural and spiritual meanings of ritual flowers qualitatively, while quantitative instruments for assessing their educational and ecological values remain limited. This study therefore developed and preliminarily evaluated a 25-item instrument covering five theoretically derived domains: Ritual Knowledge, Flower Meaning, Spiritual Value, Environmental Preservation, and Ethnopedagogy. A purposive sample of 100 respondents from Ponorogo, Banyuwangi, and Lumajang completed the questionnaire. Data were analyzed using descriptive statistics, Cronbach’s alpha, corrected item-total correlations, Spearman’s rho, principal component analysis (PCA), and hierarchical cluster analysis. Mean scores were high for Ritual Knowledge (M = 4.56, SD = 0.48), Flower Meaning (M = 4.37, SD = 0.51), Spiritual Value (M = 4.41, SD = 0.53), Environmental Preservation (M = 4.32, SD = 0.49), and Ethnopedagogy (M = 4.21, SD = 0.52). The instrument demonstrated high internal consistency (α = 0.945), with corrected item-total correlations ranging from 0.631 to 0.812. All ten interconstruct correlations were positive and significant (ρ = 0.603–0.968, p < .001), including a strong association between Environmental Preservation and Ethnopedagogy (ρ = 0.755). PCA of the five aggregate construct scores identified one dominant component with an eigenvalue of 4.18, explaining 83.6% of the total variance. The PCA and clustering results provide preliminary evidence of an integrated Ethnopedagogical-Ecological Value Dimension, while also indicating possible construct overlap. The findings support the use of seven-flower ritual knowledge as a contextual resource for biology education, ecological literacy, and cultural learning. They also inform conceptual design requirements for interactive e-book and augmented-reality media that require subsequent prototype development and classroom-based evaluation.